Leaf wound induced ultraweak photon emission is suppressed under anoxic stress: Observations of Spathiphyllum under aerobic and anaerobic conditions using novel in vivo methodology. - Carl L Oros; Fabio Alves (PLoS ONE, 2018)
Plants have evolved a variety of means to energetically sense and respond to abiotic and biotic environmental stress. Two typical photochemical signaling responses involve the emission of volatile organic compounds and light. The emission of certain leaf wound volatiles and light are mutually dependent upon oxygen which is subsequently required for the wound-induced lipoxygenase reactions that trigger the formation of fatty acids and hydroperoxides; ultimately leading to photon emission by chlorophyll molecules. A low noise photomultiplier with sensitivity in the visible spectrum (300-720 nm) is used to continuously measure long duration ultraweak photon emission of dark-adapting whole Spathiphyllum leaves (in vivo). Leaves were mechanically wounded after two hours of dark adaptation in aerobic and anaerobic conditions. It was found that (1) nitrogen incubation did not affect the pre-wound basal photocounts; (2) wound induced leaf biophoton emission was significantly suppressed when under anoxic stress; and (3) the aerobic wound induced emission spectra observed was > 650 nm, implicating chlorophyll as the likely emitter. Limitations of the PMT photocathode's radiant sensitivity, however, prevented accurate analysis from 700-720 nm. Further examination of leaf wounding profile photon counts revealed that the pre-wounding basal state (aerobic and anoxic), the anoxic wounding state, and the post-wounding aerobic state statistics all approximate a Poisson distribution. It is additionally observed that aerobic wounding induces two distinct exponential decay events. These observations contribute to the body of plant wound-induced luminescence research and provide a novel methodology to measure this phenomenon in vivo.